Free the worms! - Krulik, Nancy E. (Krulik, Nancy E. Katie Kazoo, switcheroo, 2008)
While her class is studying reptiles, Katie, a vegetarian, refuses to feed worms to Slinky the snake, class 4A's pet, but when the magic wind turns her into Slinky, Katie learns that some animals cannot survive on vegetables alone.